Study protocol for a prospective, longitudinal cohort study investigating the medical and psychosocial outcomes of UK combat casualties from the Afghanistan war: the ADVANCE Study. Issue 10 (30th October 2020) - Bennett, Alexander N; Dyball, Daniel Mark; Boos, Christopher J; Fear, Nicola T; Schofield, Susie; Bull, Anthony M J; Cullinan, Paul
Abstract : Introduction: The Afghanistan war (2003–2014) was a unique period in military medicine. Many service personnel survived injuries of a severity that would have been fatal at any other time in history; the long-term health outcomes of such injuries are unknown. The A rme D Ser V ices Tr A uma and Rehabilitatio N Out C om E (ADVANCE) study aims to determine the long-term effects on both medical and psychosocial health of servicemen surviving this severe combat related trauma. Methods and analysis: ADVANCE is a prospective cohort study. 1200 Afghanistan-deployed male UK military personnel and veterans will be recruited and will be studied at 0, 3, 6, 10, 15 and 20 years. Half are personnel who sustained combat trauma; a comparison group of the same size has been frequency matched based on deployment to Afghanistan, age, sex, service, rank and role. Participants undergo a series of physical health tests and questionnaires through which information is collected on cardiovascular disease (CVD), CVD risk factors, musculoskeletal disease, mental health, functional and social outcomes, quality of life, employment and mortality. Ethics and dissemination: The ADVANCE Study has approval from the Ministry of Defence Research Ethics Committee (protocol no:357/PPE/12) agreed 15 January 2013. Its results will be disseminated through manuscripts in clinical/academic journals and presentations at professional conferences, and through participant and stakeholder communications. Trial registration number: The ADVANCE Study is registered at ISRCTN ID: ISRCTN57285353 .